Effectiveness of Mindfulness Therapy in Reducing Guilt, Psychological Distress, and Social Isolation in Overweight Individuals - Pourrostam, Mahdieh; Khosravi Hampa, Ali Akbar; Ganjali, Zeinab (Health Nexus, 2023)
This study aimed to examine the structural relationships between attachment styles and social anxiety in adolescents dependent on internet games, considering the mediating role of loneliness. A random sample of 200 adolescents dependent on internet games was selected, and questionnaires on attachment style, social anxiety, and loneliness were completed for them. The results showed that a secure attachment style directly and indirectly leads to reduced social anxiety through decreased loneliness. Additionally, avoidant and anxious-ambivalent attachment styles directly and indirectly lead to increased social anxiety through heightened loneliness. These findings indicate that loneliness plays a significant mediating role in the relationship between attachment styles and social anxiety in adolescents dependent on internet games.